1960
DOI: 10.1111/j.1365-2141.1960.tb06223.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies of Bone‐Marrow Cells in the Early Stages of Final Haemopoietic Recovery in Irradiated Guinea‐pigs

Abstract: NORMAL active bone marrow is a complex structure in which it is difficult to study microscopically the early precursors of granulocytes and erythroid cells. By using a suitable dose of whole-body irradiation the cellularity of the marrow can be considerably decreased and simplified since the more mature cells, which form the majority of the marrow cells, are eventually eliminated. During recovery of the bone marrow from irradiation of this degree the stem-cell population can be easily stuhed in the initial sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
2

Year Published

1963
1963
1972
1972

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
4
22
2
Order By: Relevance
“…The latter observation confirmed the findings of H a rris [3,5] in guinea pigs. The rise in marrow lymphocytes has been shown to depend on the dose of irradiation [12].…”
Section: Red Cell Precursorssupporting
confidence: 81%
“…The latter observation confirmed the findings of H a rris [3,5] in guinea pigs. The rise in marrow lymphocytes has been shown to depend on the dose of irradiation [12].…”
Section: Red Cell Precursorssupporting
confidence: 81%
“…What is the significance of this rapidly changing X-cells population? It is likely that these cells are the same as the lymphoid cells called 'transitional cells' by other authors which assume a relation between the transitional cells and other marrow elements [3,4,5,6,10]. The present results are in contradiction with this assumption.…”
Section: Discussioncontrasting
confidence: 57%
“…Particular attention has been drawn on the accumulation of small mononucleated cells in the bone-marrow of animals recovering from an irradiation [3,4]. These cells, morpho logically similar to the lymphocyte from which they can nevertheless be distinguished by some cytological characters, have received the name o f'transitional cells' [5,6].…”
mentioning
confidence: 99%
“…Large numbers of lymphocytes accumulate in the marrow before the substantial recovery of erythropoiesis and granulopoiesis (15). The accumulation is not restricted to guineapigs.…”
mentioning
confidence: 95%
“…Previous studies of bone marrow in sub-lethally irradiated guinea-pigs (15) have shown that there is a characteristic phase before the final recovery of granulopoiesis and erythropoiesis. At this time large numbers of mononuclear cells of various sizes are present, and many of them resemble small lymphocytes.…”
Section: By P F H Arris G H Aigh and J H K Uglermentioning
confidence: 99%